La plaza roja la concepción de riobamba como espacio de identidad cultural y su incidencia en la opinión pública de los habitantes entre 45-65 años de la parroquia Velasco durante el periodo enero a diciembre 2016 - Mosquera Perdomo, Karol Magaly (2017)
The present project aims to analyze the public opinion of the inhabitants of the parish Velasco between 45-65 years in relation to the “La Plaza Roja de La Concepción” as a space of cultural identity in the period January to December 2016. The Red Square is located in this Place of 1799 after the earthquake that destroyed the old Riobamba, with the mandate of Former Mayor Edelberto Bonilla the artisans were transferred to this place. The theoretical framework compiles the foundations and theories necessary to support the research. There, different concepts of authors are broadened and analyzed on topics such as: Riobamba, “La Plaza Roja”, cultural identity, identity, culture, cultural anthropology, Public Opinion and age groups. The methodology used was the scientific method that allowed to know the history and current situation of the Red Square, through theoretical foundation and data collection as surveys. This research project was carried out with the support of the inhabitants of the Velasco parish by means of a survey. The results were then analyzed and interpreted, and then conclusions and recommendations were made, describing the factors that allow the citizens of This parish feel identified with the Red Square. Finally, it was proposed a Catalog of handicrafts of the Red Square itself whose purpose is for the citizens to know the elaboration and meaning of the handicrafts that are marketed in “La Plaza Roja” and in this way to remain in place as a purely artisanal market .